Mapping Community-Based Tourism Potentials in Semi-Urban Villages: A Triangulated Approach - Tomy Andrianto; Eko Susanto; Any Ariani Noor; Marceilla Suryana; Deisy Christina Andih (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
This study analyzes the potential of Community-Based Tourism (CBT) within a semi-urban village context, addressing a gap in the tourism literature that predominantly focuses on rural areas. Using an integrative qualitative approach, the research combines participatory mapping, in-depth interviews, and Focus Group Discussions (FGDs) in Ciwaruga Village, West Bandung Regency. The study triangulates perspectives from three local pillars: government, community, and academia. Data collection involved 10 key informants, approximately 20 FGD participants, and four rounds of field observations. Findings reveal that semi-urban tourism relies on scattered "micro-attractions" (natural, cultural, and artificial) rather than a single iconic site. While community readiness is characterized as "emergent", marked by high enthusiasm but low institutional structure, the study identifies that participatory mapping acts as a social technology to bridge this gap. The research concludes that a tri-pillar collaborative governance model is essential to transform semi-urban complexity into sustainable tourism destinations.